1999
DOI: 10.1034/j.1399-3003.1999.14d22.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway inflammation in children exposed to ambient ozone and potential signs of adaptation

Abstract: In order to investigate nasal inflammation and subsequent adaptation after ambient ozone exposure, nasal lavage (NL) fluid was collected from 170 schoolchildren on 11 occasions (time points) between March and October.Eosinophil cationic protein (ECP), albumin and leukocytes were quantified as markers of nasal inflammation. The highest half-hour outdoor O 3 concentration for each individual on the day prior to the NL was used as a measure of exposure (O 3 indiv). To avoid confounding with exposure to common env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 38 publications
0
17
1
2
Order By: Relevance
“…Previous epidemiologic works have found that NALF inflammatory mediators are related to ETS exposure in children 42 and to ozone levels, 43 but none of them demonstrated leukocyte increase in relation to ambient PM10 exposures. 17,18,26,27 When PM10 concentrations were introduced in our multivariate models, we also failed to evidence any association between outdoor PM10 levels and nasal mediators (data not shown). These results indicate that environmental measurements of PM10 might not be relevant for study of respiratory inflammation.…”
Section: Issues On Associationscontrasting
confidence: 51%
See 1 more Smart Citation
“…Previous epidemiologic works have found that NALF inflammatory mediators are related to ETS exposure in children 42 and to ozone levels, 43 but none of them demonstrated leukocyte increase in relation to ambient PM10 exposures. 17,18,26,27 When PM10 concentrations were introduced in our multivariate models, we also failed to evidence any association between outdoor PM10 levels and nasal mediators (data not shown). These results indicate that environmental measurements of PM10 might not be relevant for study of respiratory inflammation.…”
Section: Issues On Associationscontrasting
confidence: 51%
“…In all previous works, assessment of PM exposure has been based on fixed-site measurements of particulate matter with a diameter of less than 10 mm (PM10), 17,18,26,27 which reflect only a part of the true exposure. In this work PM2.5 exposure, now regarded as the state of the art in the field of environmental epidemiology, [28][29][30] was measured in a personal manner to limit misclassifications.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…In rats, the respiratory responses (rapid shallow breathing and decreased lung function) adapt despite the continued presence of lung epithelial damage, inflammation, increased concentrations of lavagable proteins (24), and increased sensory nerve excitability (30,32), suggesting that lung-CNS reflexes might be involved in the adaptation. Of direct relevance to the present study is that the adaptation is not just limited to adults but also occurs earlier in life (37,38).…”
mentioning
confidence: 94%
“…27). The airway inflammatory cell profile of ozone is predominantly neutrophilic in adult humans and most animal models; however, there is evidence that children develop an eosinophilic response to ambient levels of exposure (14,35,36). Because of the nonantigenic nature of ozone, there is currently no evidence that an adaptive immune response leading to establishment of immunological memory and antibody production is induced by exposure alone.…”
mentioning
confidence: 95%